The Influence of Servant Leadership and Intrinsic Motivation on Employee Performance Through Organizational Commitment in Subdistrict Government Institutions - Zahari, M.; Yamali, Fakhrul Rozi; Hartono, Hartono (Dinasti International Journal of Management Science, 2024)
This research aims to determine and analyze the influence of servant leadership and intrinsic motivation on employee performance through organizational commitment in Subdistrict Government Institutions. The method used in this research is descriptive verification and quantitative methods. The object of research in this study is the Influence of Servant Leadership and Intrinsic Motivation on Employee Performance Through Organizational Commitment in Jelutung Sub District Government, Jambi City. In this research, the sampling technique used was a nonprobability sampling approach with a purposive sampling method. Based on the approach, it can be seen that the number of samples is 56 people. This research uses the PLS analysis method. Based on data processing, Servant Leadership is in the serving category. Then, to describe the Intrinsic Motivation variable, it shows that the Intrinsic Motivation of employees in Subdistrict Government Institutions is high. Next is a description of the Organizational Commitment variable in the high category. Meanwhile, an overview of employee performance variables in the high category. Based on the research results, Servant Leadership has a positive and significant effect on Organizational Commitment, Intrinsic Motivation has a positive and significant effect on Organizational Commitment, Servant Leadership has a positive and significant effect on employee performance, Intrinsic Motivation has a positive and significant effect on employee performance, Organizational Commitment has a positive and significant effect on employee performance, Servant Leadership has a significant and positive effect on employee performance through Organizational Commitment and Intrinsic Motivation has a significant and positive effect on employee performance through Organizational Commitment in SubDistric Government.